Capixabandos e conversações e jurisprudências em frente à prescrição curricular no Espírito Santo: o Congo como máquina de guerra nômade - Soeiro, Lucas Borges (2022)
This research intends to invent micropolitics and jurisprudence with a public school that try to subvert the determinisms of the prescriptions “Base Nacional Comum Curricular” (BNCC) and “Currículo do Espírito Santo” (CES), a product of the Base in the Espírito Santo context. As a theoretical-epistemological reference, it bets on Certeau's studies of everyday life, mainly to understand the uses that teachers have made of the aforementioned curricular prescriptions. It values the creative and immanent force of difference, using Deleuze and Guattari as theoretical intercessors that make us think about the school and its escapes from arboreal models, especially when they allow us to delirious with the power of signs, especially those we insist on calling Espírito Santo signs. These appear in the research as triggers that evoke the strength of the cultural productions of resistance of native and black peoples in the face of the absurdities imposed in the colonizing processes. It is in this gap that we make use of the Espírito Santo signs, above all, the Congo, as an inventive policy, as a Nomadic War Machine that summons the people of Espírito Santo to resist, create and achieve an artistic dimension in the face of the perversities of the State Machine that has been established since 1535 in Espírito Santo territory. In this game, conceptual characters are placed between the lines of writing to make us think about the resonances that our bodies take in face of the curricular disputes of the instituted-instituting movements, these are the capixabandos and the jaguars. As a methodological framework, we bet on the political-epistemological-inventive dimension of research with everyday life, which advocates in favor of capixabans for not conceiving capixabas as passive, docile or submissive, but as those who produce curriculum policies and help us to away from the jaguar states that try to hatch in our bodies during research. This research points to the existence of a jurisprudential movement that exists in schools because the legislating jaguars and the esturros colonizers of the norms end up trying to kill lives with limitations, generalities and intentions in the service of capital. Thus, jurisprudence demarcates the indispensability of everyday conversations for decisions to take action for life, raising the instituting power, whose people are the holder, as a suggestion, including the dispensability of curricular prescriptions and writings riddled with death.